A global analysis of Y-chromosomal haplotype diversity for 23 STR loci - Purps, Josephine; Siegert, Sabine; Willuweit, Sascha; Nagy, Marion; Alves, Cíntia; Salazar, Renato; Angustia, Sheila M T; Santos, Lorna H; Anslinger, Katja; Bayer, Birgit; Ayub, Qasim; Wei, Wei; et al. (Forensic science international. Genetics, 2014)
In a worldwide collaborative effort, 19,630 Y-chromosomes were sampled from 129 different populations in 51 countries. These chromosomes were typed for 23 short-tandem repeat (STR) loci (DYS19, DYS389I, DYS389II, DYS390, DYS391, DYS392, DYS393, DYS385ab, DYS437, DYS438, DYS439, DYS448, DYS456, DYS458, DYS635, GATAH4, DYS481, DYS533, DYS549, DYS570, DYS576, and DYS643) and using the PowerPlex Y23 System (PPY23, Promega Corporation, Madison, WI). Locus-specific allelic spectra of these markers were determined and a consistently high level of allelic diversity was observed. A considerable number of null, duplicate and off-ladder alleles were revealed. Standard single-locus and haplotype-based parameters were calculated and compared between subsets of Y-STR markers established for forensic casework. The PPY23 marker set provides substantially stronger discriminatory power than other available kits but at the same time reveals the same general patterns of population structure as other marker sets. A strong correlation was observed between the number of Y-STRs included in a marker set and some of the forensic parameters under study. Interestingly a weak but consistent trend toward smaller genetic distances resulting from larger numbers of markers became apparent.
Keywords: alely; Alleles; lidé; Forensic Genetics; haplotypy; Chromosomes, Human, Y; lidský chromozom Y; mikrosatelitní repetice; Haplotypes; soudní genetika; Microsatellite Repeats; Humans